Analisis Variabel Makro yang Mempengaruhi IHSG - Sasono, Heri; Syukri, Ahmad (STAI Denpasar Bali, 2023)
Investors always expect profit in investing their capital in the Capital Market, especially on the Indonesian Stock Exchange (IDX). The purpose of this study was to analyze the effect of macro variables on the Jakarta Composite Index (IHSG) for the period 2010 to 2021. The macro variables used in this study were inflation, economic growth, dollar exchange rates and SBI (7-Day Reverse Repo Rate). The years that were used as research samples were 12 years, from 2010 to 2021. The research analysis used multiple linear regression analysis, t test, F test, test the coefficient of determination using SPSS Version 26 software.The conclusion of the study is that Economic Growth, Dollar Exchange Rate and SBI (7-Day Reverse Repo Rate) have a significant effect on the JCI, while Inflation has an insignificant effect on the JCI. Then simultaneously Inflation, Economic Growth, Dollar Exchange Rate and SBI have a significant effect on the JCI.